Anomalous positive pyrite sulfur isotope in lacustrine black shale of the Yanchang Formation, Ordos Basin: Triggered by paleoredox chemistry changes. (November 2020) - Chen, Guo; Chang, Xiangchun; Gang, Wenzhe; Wang, Ning; Zhang, Pengfei; Cao, Qingyun; Xu, Jianbin
Abstract: The pyrite sulfur isotope in the black shale of the Chang 7 unit are anomalous positive compared with those of the current paradigm, in which the value of pyrite sulfur isotopes should be negative due to sulfur isotopic fractionation through bacterial sulfate reduction (BSR). A series of geological and geochemical analysis (FeT /Al and δ 34 Spy, average of 0.51 and 6.5‰, respectively) are carried out to confirm that sulfur speciation is derived from sulfate in watermass rather than hydrothermal fluids, and the δ 34 Spy values are effective records of the original sedimentary environment. Integrated geochemical data including redox sensitive elements (RSE) ratios, ratio of organic carbon to phosphorus (Corg :P, molar, average of 85.4), organic sulfur to carbon (organic S:C, average of 10.47%) and pyrite framboid size distribution (range in 9.7–16.6 μm), are represented to reconstruct the paleoredox chemical conditions during the deposition of the Chang 7 unit black shale. The results suggest that the paleoredox chemical conditions of the middle and lower subunits (the Ch 72 and Ch 73 subunits) were dominated by suboxic environments with intermittent anoxic environments and that changed to oxic with intermittent suboxic environments in the upper subunit (the Ch 71 subunit). Based on the analysis of sulfur isotope fractionation during the sulfur cycle, the paleoredox chemical conditions are confirmed to be the trigger for the anomalous sulfur isotopic compositions. The limited sulfate in watermass and overlying fine-grained sediments resulted in a relatively closed system for BSR, where limited sulfur isotope fractionation lead to the formation of heavy pyrite. Subsequently, due to the dissolved oxygen penetrated into the sediment, the reactivation of anaerobic oxidants resulted in reoxidation of hydrogen sulfide derived from BSR, then to "heavier" pyrite via Rayleigh-type distillation in the Ch 71 subunit. Highlights: The paleoredox conditions of the Ch7 unit changed from suboxic to oxic upwardly. BSR occurring in a closed system led to positive δ 34 Spy values in the Ch7 unit. Reactivation of anerobic oxidant formed "heavier" pyrite in the upper Ch7 unit.